Cortical Thinning Mediates the Correlation between Periventricular White Matter Hyperintensities and Cognitive Impairments - Wenjie Zi; Jian Zheng (International Journal of Medical Research, 2013)
Introduction: Previous studies showed that white matter lesions (WMLs) were an important risk factor for cognitive impairment, but the mechanisms whereby WMLs induced cognitive impairment have not been clarified. We hypothesised that the correlation between WMLs and cognitive impairments would be mediated by cortical thinning. Methods: Patients with periventricular white matter hyperintensities (PWMHs) on MRI were selected as research subjects. We investigated the contributions of PWMHs to several domains of cognitive impairment and the topography of cortical thinning and then investigated the relationship among diffusion tensor imaging (DTI) measurements, cortical thinning, and cognitive impairments. Participants included 16 stroke- and dementia-free subjects with PWMHs on magnetic resonance imaging (MRI) and 20 healthy control subjects. All participants underwent an examination of cognition, cortical thickness, and a DTI scan. Results: After accounting for age, sex, years of education, and treatable cardiovascular risk factors related to cognitive performance, DTI measurements of periventricular WMLs were associated with cognitive impairment in executive function and verbal fluency and with cortical thinning in the frontal pole, orbitofrontal cortex, superior and middle frontal gyri, superior and middle temporal gyri, insula, lingual gyrus, and cuneus. Cortical thinning, but not PWMH, was independently associated with cognitive impairment. Conclusion: Our results suggest that the correlation between PWMHs and cognitive impairments is mediated by cortical thinning.